2023
DOI: 10.31234/osf.io/yx4s8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A systematic review of cultural adaptations of the Positive Affect and Negative Affect Schedule (PANAS)

Abstract: Background: The Positive Affect and Negative Affect Schedule (PANAS) has been used worldwide as a valid and consistent instrument to investigate the bidimensional structure of affect. Researchers can adapt PANAS from English to other languages by developing a new scale or translating directly from the original. This review describes and evaluates the currently available PANAS translations according to instrument transcultural adaptation standards. We sought to improve the reliability and quality of transcultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Versatility, psychometric properties, and cross-cultural validity are the positive aspects. Many studies employed the PANAS method and validated it in different languages and cultural contexts, such as Spanish, Chinese, and Polish, indicating its versatility and applicability across diverse populations [14]. Research has demonstrated the psychometric properties of the PANAS, including good internal consistency and reliability [4,15].…”
Section: Positive and Negative Affect Schedule (Panas)mentioning
confidence: 99%
“…Versatility, psychometric properties, and cross-cultural validity are the positive aspects. Many studies employed the PANAS method and validated it in different languages and cultural contexts, such as Spanish, Chinese, and Polish, indicating its versatility and applicability across diverse populations [14]. Research has demonstrated the psychometric properties of the PANAS, including good internal consistency and reliability [4,15].…”
Section: Positive and Negative Affect Schedule (Panas)mentioning
confidence: 99%